Mechanism and Durability of Repair Systems in Polymer-Modified Cement Mortars - Ru Wang (Advances in Materials Science and Engineering, 2015)
This paper investigated the mechanism and durability of repair systems made of ordinary cement-based repair mortar and three kinds of polymer-modified repair mortars with old concrete, SBR dispersion, SAE dispersion, and SAE powder. By comparing the bonding properties of mortars before and after erosion, it was found that polymers could effectively improve the durability of the repair system and SAE powder had the best improvement. Micromorphology study of the repair mortar and the interface of repair mortar with old concrete through SEM showed that the polymer film formed from SAE powder whatever in the mortar or at the interface was dense and tough, the film formed from SAE dispersion was loose and weak, while the film formed from SBR dispersion was in between them, which explained the difference in the tensile bond strength and the durability of the repair systems.